2013
DOI: 10.1007/s10803-013-2012-7
|View full text |Cite
|
Sign up to set email alerts
|

Autistic Traits and Abnormal Sensory Experiences in Adults

Abstract: Sensory processing abnormalities are common in autism spectrum disorders (ASD), and now form part of the Diagnostic and Statistical Manual 5th Edition (DSM-5) diagnostic criteria, but it is unclear whether they characterize the ‘broader phenotype’ of the disorder. We recruited adults (n = 772) with and without an ASD and administered the Autism Quotient (AQ) along with the Adult/Adolescent Sensory Profile (AASP), the Cardiff Anomalous Perceptions Scale (CAPS), and the Glasgow Sensory Questionnaire (GSQ), all q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
150
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(178 citation statements)
references
References 40 publications
(59 reference statements)
24
150
1
3
Order By: Relevance
“…For the AQ, such gender differences are expected, based on the sex ratio in diagnosing ASD (Baron-Cohen et al, 2001). The gender difference in the total AQ score was consistent with the result of previous studies (Austin, 2005;Baron-Cohen et al, 2001;Hoekstra et al, 2008;Horder et al, 2014;Robertson & Simmons, 2013;Stewart & Austin, 2009;. For the GSQ, this study is the first to report gender differences.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…For the AQ, such gender differences are expected, based on the sex ratio in diagnosing ASD (Baron-Cohen et al, 2001). The gender difference in the total AQ score was consistent with the result of previous studies (Austin, 2005;Baron-Cohen et al, 2001;Hoekstra et al, 2008;Horder et al, 2014;Robertson & Simmons, 2013;Stewart & Austin, 2009;. For the GSQ, this study is the first to report gender differences.…”
Section: Discussionsupporting
confidence: 90%
“…The original study of the GSQ showed a significant positive correlation between GSQ and AQ scores in the general population (Robertson & Simmons, 2013). In addition, a score difference between individuals with ASD and those without ASD was found (Horder, Wilson, Mendez, & Murphy, 2014). Furthermore, Horder et al (2014) compared the correlation between scores of the AQ, GSQ, and AASP, and revealed that the correlation between the AQ and GSQ was the strongest.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Robertson and Simmons (2012) assessed sensory sensitivities in the BAP in several modalities (including auditory, tactile, and olfactory) and reported that higher levels of autistic traits were associated with higher levels of sensory behaviors across each of these domains. More recently, Horder, Wilson, Mendez, and Murphy (2014) have replicated these findings in a larger scale study, showing a linear relationship between autistic traits and sensory scores. Furthermore, they were able to replicate this relationship across three different measures of sensory behaviors.…”
Section: Research-article2015supporting
confidence: 55%
“…As such, taking measures to modify the environment could make accessibility easier for individuals with ASD, and could potentially minimise distress in uncomfortable situations. Indeed, it may be the case that small adjustments to the environment could be helpful to many people in the general population, as evidence suggests that individuals with elevated, albeit subclinical, levels of autistic traits report atypical sensory perception (Horder, Wilson, Mendez, & Murphy, 2014;Robertson & Simmons, 2013, Uljarevi• et al, 2014.…”
Section: Practical Implications Of the Findingsmentioning
confidence: 99%